A New Delhi metallo-β-lactamase (NDM)-positive isolate of Klebsiella pneumoniae causing catheter-related bloodstream infection in an ambulatory hemodialysis patient - Kevin H. Toomer; Daniela de Lima Corvino; Katie A. McCrink; Jose Armando Gonzales Zamora (IDCases, 2020)
The New Delhi metallo-β-lactamase (NDM) is a mediator of broad antimicrobial resistance among the Enterobacteriaceae and other gram-negative pathogens that cause opportunistic and nosocomial infections. In the decade since its discovery, NDM has spread worldwide and represents an increasing threat to public health. NDM is capable of hydrolyzing nearly all known β-lactam antibiotics, including the carbapenems, and due to its zinc ion-dependent catalytic mechanism is unaffected by available β-lactamase inhibitors. We report a case of catheter-related bloodstream infection caused by a pan-resistant, NDM-positive isolate of Klebsiella pneumoniae in an ambulatory end-stage renal disease patient started on hemodialysis approximately 8 weeks prior. The absence of any recent hospitalization indicates that the infection was likely acquired from a hemodialysis center in the United States. This case demonstrates the increasing prevalence of antimicrobial resistance mechanisms in ambulatory as well as inpatient healthcare settings, and highlights the particular risk of the outpatient hemodialysis facility as an optimal environment for colonization with multidrug- and pandrug-resistant pathogens.